2016
DOI: 10.1530/erc-16-0123
|View full text |Cite
|
Sign up to set email alerts
|

Lymphovascular invasion is associated with survival for papillary thyroid cancer

Abstract: Data are limited regarding the association between tumor lymphovascular invasion and survival for patients with papillary thyroid cancer (PTC). This study sought to examine lymphovascular invasion as an independent prognostic factor for patients with PTC undergoing thyroid resection. The National Cancer Data Base (2010-2011) was queried for patients with PTC who underwent total thyroidectomy or lobectomy. Patients were classified into two groups based on the presence/absence of lymphovascular invasion. Demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 17 publications
5
26
2
Order By: Relevance
“…In another study, LVI was determined in 4.9% of PTC patients (n = 662) [38]. The largest study investigating the association between LVI and PTC was published by Pontius et al [25]. The authors reported 11.6% incidence of LVI in PTC patients [25].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In another study, LVI was determined in 4.9% of PTC patients (n = 662) [38]. The largest study investigating the association between LVI and PTC was published by Pontius et al [25]. The authors reported 11.6% incidence of LVI in PTC patients [25].…”
Section: Discussionmentioning
confidence: 98%
“…In another study conducted by Xu et al [22], extensive vascular invasion (EVI) was an independent predictor of poor recurrence-free survival in low-grade encapsulated follicular cell-derived thyroid carcinomas (LGEFCs), and patients with EVI may be considered for more aggressive treatment modalities. Data on the association between LVI and clinicopathological features of PTC are limited to small case series, and conflicting results have been reported [23][24][25][26]. In this study, we investigated the relationship between the presence of LVI and clinical features and histopathological outcomes of PTC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrence rates have been reported to be as high as 20–30%, and more than 10% of patients die as a result of disease progression [5, 6]. Some patient-related factors such as advanced age at diagnosis, larger tumor size, cervical lymph node metastases, extrathyroidal extension, and lymphovascular invasion have been associated with an increased risk of disease progression at a population level, but they lack the precision to perfectly tailor surveillance and treatment strategies and anticipate prognosis [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Definitions of LVI vary from author to author, and there are issues of overdetection with artifacts, all of which contribute to the confusion regarding this particular pathologic finding [6]. In other malignancies, such as thyroid [7], lung [8], stomach [9], bladder [10], kidney [11], and breast cancers [12], LVI is considered as an independent prognostic factor. Regarding the prostate, despite the unclear prognostic value of LVI in prior studies conducted in the general population, more recent investigations of patients in particular stages show some promising aspects [1, 13, 14].…”
Section: Introductionmentioning
confidence: 99%